Randomised controlled trials in severe asthma: selection by phenotype or stereotype. Issue 6 (13th December 2018) - Brown, Thomas; Jones, Thomas; Gove, Kerry; Barber, Clair; Elliott, Scott; Chauhan, Anoop; Howarth, Peter
Previous publications have highlighted the disparity between research trial populations and those in clinical practice, but it has not been established how this relates to randomised controlled trials (RCTs) of phenotype-targeted biological therapies in severe asthma. Detailed characterisation data for 342 severe asthma patients within the Wessex Severe Asthma Cohort (WSAC) was compared against comprehensive trial eligibility criteria for published phase IIB and phase III RCTs evaluating biological therapies in severe asthma since 2000. 37 RCTs evaluating 20 biological therapies were identified. Only a median of 9.8% (range 3.5–17.5%) of severe asthma patients were found to be eligible for enrolment in the phase III trials. Stipulations for airflow obstruction, bronchodilator reversibility and smoking history excluded significant numbers of patients. A median of 78.9% (range 73.2–86.6%) of patients with severe eosinophilic asthma would have been excluded from participation in the phase III licensing trials of interleukin (IL)-5/IL-5R targeted therapies. Despite including only well characterised and optimally treated severe asthmatics under specialist care within the WSAC study, the vast majority were excluded from trial participation by criteria designed to re-confirm diagnostic labels rather than by biomarker criteria that predict the characteristic addressed by the treatment. RCTs of biological therapies in severe asthma are poorly generalisable with most patients excluded by outmoded disease concepts despite possessing the targetable trait addressed by the treatment http://ow.ly/iog930md0J3